LABORATORY CHARACTERISTICS OF PATIENTS WITH LIVER CIRRHOSIS OF VIRUS ETIOLOGY COMPLICATED WITH SPONTANEOUS BACTERIAL PERITONITIS - Oblokulov A.R; Oblokulova O.A; Bahronov O. O (PT. Antis International Publisher, 2024)
Background: Systemic inflammation plays a crucial role in the pathophysiology of various diseases, particularly in patients with liver cirrhosis. Specific Background: The Neutrophil-to-Albumin Percentage Ratio (NPAR) has emerged as a novel biomarker for assessing systemic inflammation. Low serum albumin levels combined with elevated neutrophil counts have been associated with an increased risk of infections, including spontaneous bacterial peritonitis (SBP), a serious complication in cirrhotic patients. Knowledge Gap: Despite the recognized risks and mortality associated with SBP, the specific role of NPAR in predicting outcomes in patients with cirrhotic ascites remains underexplored. Aims: This study aims to evaluate the predictive value of NPAR in identifying patients at high risk for developing SBP and to assess its association with in-hospital mortality rates. Results: Our findings indicate that elevated NPAR is significantly correlated with the incidence of SBP and is associated with higher in-hospital mortality, reinforcing the potential of this biomarker in clinical practice. Novelty: This research provides new insights into the utility of NPAR as a predictive tool for SBP in cirrhotic patients, potentially guiding clinicians in early diagnosis and intervention. Implications: By highlighting the importance of NPAR, this study advocates for its incorporation into routine clinical assessments to improve patient outcomes, emphasizing that timely diagnosis and appropriate treatment of SBP can significantly reduce mortality rates.